Inhibitory Effect of Extract from Twelve Chinese Medical Herbs and Two Active Quaternary Protoberberine Alkaloid from Coptis chinensis Franch - Chen, Long; Zhou, Wei; Wu, Lang; Gao, Manlu; Hou, Taiping; Tao, Ke (Asian Journal of Chemistry, 2013)
The traditional Chinese medical plants had been used for many centuries to support the immune system or to fight human infections. Among them, the phytochemicals of many herbs might suggest the possibility of their exploitations to the botany fungicides. In this study, twelve herbs used in the treatment of infectious diseases in traditional Chinese medicine were evaluated for in vitro activity against sixteen microbial plant pathogens. Among them, eleven were plant-pathogenic fungi and five were bacteria. All of the EtOH extracts were tested by the agar dilution technique. From the assessment of the crude extracts, the Coptis chinensis Franch were active against at least two microorganisms, especially to the Valsa mali Miyabe et Yamada. With the isolation and purification of Coptis, we finally obtained two pure antifungal active alkaloids i.e., berberine and palmatine. And their resistances to the Valsa mali Miyabe et Yamada showed that the 50 % effective concentration (EC50) of the berberine reached 9.84 ppm and the EC50 of palmatine was 243 ppm.